ASPEK FEMINIMITAS, TEKANAN KETAATAN, DAN KOMPLEKSITAS TUGAS DALAM PERTIMBANGAN AUDIT - WIDJAYA, UNTUNG (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
An auditor to consider materiality and risk of misstatement when audited financial statements. Dipergaruhi consideration some aspects such as: obedience pressure, task complexity and gender aspects of both masculinity and femininity. Compliance pressures will impact on auditor performance because the form of orders from the boss that is not appropriate in addition, high complex task of an auditor to auditor dysfunctional behavior. Femininity played when there is pressure and compliance at the time of audit task complexity. a woman would be able to receive orders, more accurately, and controlling your emotions, so that the audit will take into account the lower risk and more cautious. This paper explains that the auditor will be able to consider the woman a better audit.